THE "KROPYVA" SOFTWARE COMPLEX AS AN ELEMENT OF THE PROSPECTIVE AUTOMATED CONTROL SYSTEM OF THE NATIONAL GUARD OF UKRAINE - Horelyshev, Stanislav; Ivchenko, Artem; Bashkatov, Yevhen (Honor and Law, 2023)
The article deals with the use of the "Kropyva" software complex as an element of the prospective automated control system of the National Guard of Ukraine (NGU). Automated troop management systems significantly increase the effectiveness of the process of preparation and military decision-making through the use of accelerated analysis and generalization of information about enemy forces and assets, own forces, and terrain. In fact, instant simulation of various scenarios takes place, and artificial intelligence automatically deduces the most appropriate one in these conditions. Starting from 2018, individual elements of tactical-level information systems were used ‒ "Delta", "Kropyva", "Virazh-tablet", "GisArta" and others. For the tasks of NGU, the software "Kropyva" is of interest ‒ a actical link management system based on GIS for creating intelligent maps in combination with devices and instruments, for planning, calculations and orientation on the terrain. The analysis of the functional capabilities of the software complex in solving the tasks of the service and combat activity of the NGU was carried out. It is proposed to use the functionality of the software " Kropyva" when solving the tasks of orientation on the terrain, performing topogodetic calculations, plotting the tactical situation and exchanging this information between users, as well as managing the battle. Currently, there are several types of automated workplace that perform tasks according to their level ‒ the commander's automated workplace is stationary and the automated workplace is mobile. Recommended recommendations for the use of automated workplaces on the basis of the "Kropyva" in the performance of service-combat (combat) tasks by units and parts of the NGU. It is emphasized that the direct adjustment of the software "Kropyva" system and the corresponding automated workplace should be carried out only after other necessary measures for organizing management and establishing communication.